2001
DOI: 10.1002/jmri.1127
|View full text |Cite
|
Sign up to set email alerts
|

Development, standardization, and testing of a lexicon for reporting contrast‐enhanced breast magnetic resonance imaging studies

Abstract: The purpose of this study was to develop, standardize, and test reproducibility of a lexicon for reporting contrastenhanced breast magnetic resonance imaging (MRI) examinations. To standardize breast MRI lesion description and reporting, seven radiologists with extensive breast MRI experience developed consensus on technical detail, clinical history, and terminology reporting to describe kinetic and architectural features of lesions detected on contrastenhanced breast MR images. This lexicon adapted American C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
0
12

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 22 publications
(25 reference statements)
7
170
0
12
Order By: Relevance
“…Perfusion effects already cause a substantial signal attenuation at low b-values, which explains the contribution of mainly perfusion effects to the ADC when only low b-values are used. Prior studies reported that the contribution of perfusion effects to the ADC are larger than diffusion effects (15,16). Because perfusion effects are already present at low bvalues, the ADC at low b-values is higher than the ADC obtained with higher b-values.…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 89%
See 1 more Smart Citation
“…Perfusion effects already cause a substantial signal attenuation at low b-values, which explains the contribution of mainly perfusion effects to the ADC when only low b-values are used. Prior studies reported that the contribution of perfusion effects to the ADC are larger than diffusion effects (15,16). Because perfusion effects are already present at low bvalues, the ADC at low b-values is higher than the ADC obtained with higher b-values.…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 89%
“…A promising adjunct MRI technique is diffusion-weighted imaging (DWI) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In DCE Breast MRI, lesions are characterized based on morphology, internal enhancement, and kinetic enhancement pattern (16,17). With DWI, the cellularity of a lesion can be indirectly assessed.…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 99%
“…In an attempt to correlate the shape parameters described in this work with a familiar and commonly used lexicon system, we scored each lesion according to their BI-RADS (MRI) classification (11). Lesions were divided into mass or non-mass-like enhancement.…”
Section: Methodsmentioning
confidence: 99%
“…Various lexicons have been introduced to categorize the morphological appearance of focal enhancement, such as that recently proposed by a breast lesion diagnosis working group (10,11). This group subclassified both shape and margin into several distinct types in an attempt to standardize reporting and help identify common architectural features.…”
mentioning
confidence: 99%
“…The initial enhancement phase is further categorized into fast, medium, and slow. The late enhancement phase is described as persistent, plateau, and washout [12][13][14][15][16].…”
Section: Interpretation Of Mr Imagingmentioning
confidence: 99%